Participação de células B-1b noprocesso de cicatrização no camundongo - Oliveira, Helena da Cruz [UNIFESP] (2010)
Wound healing is a complex phenomenon whose mechanisms are not fully understood. There are no reports concerning the participation of B lymphocytes in tissue repair. However, Almeida et al (Inter Immunol, 2001) demonstrated that B-1 cells proliferate in stationary culture of adherent peritoneal cells. Further, that B-1 cells migrate to non-specific inflammatory focus and differentiate into a mononuclear phagocyte. B-1 cells differ from conventional B cell by its anatomical location, ontogeny, surface markers expression, production of antibodies and growth properties. B-1 cells are present in the peritoneal and pleural cavities and rare in the spleen and absent in the lymph nodes of adult mice. It has been reported that these cells secret large amounts of IL-10 and this cytokine play a role in the wound healing process. Aim: Investigate the participation of B-1 cells in the wound healing process in mice. Methods: That B-1 cells migrate to the wound was evaluated using immunofluorescence technique. The fluorescence activated cell sorter was used to detect B-1b cells in pleural and peritoneal cavities from BALB/c, BALB/Xid and BALB/Xid adoptively transferred with B-1 cells. The dorsal lesions were made to compare the time of the wound healing process in differs groups. The influence of B-1 cells in the neutrophilic infiltration and the angiogenic process was evaluated by imunohistochemical techniques. Moreover, the kinetics of the inflammation in mice footpads was made to evaluate the role of B-1 cells in the inflammatory phase of tissue repair. The same technique of the dorsal lesion and dorsal lesion footpad were made in IL-10 Knock-out and IL-10 Knock-out adoptively transferred with B-1 cells in order to investigate the participation of IL-10 secreted by B-1 cells in this process. Finally, using fluorescence activated cell sorter secretion of growth factors by B-1 cells was analyzed. Results: B-1 cells migrate to the inflammatory site of the wound healing process. B-1b cells participate in wound healing process and influence the inflammatory phase of this process. Moreover, B-1b cells influence neutrophilic infiltration and the angiogenic process. In addition, B-1 cells modulate the inflammatory phase of tissue repair secreting IL-10, FGF, TGF-β and MCP-1. Conclusion: These data indicate that B-1 cells participate of the inflammatory phase of the wound healing process. Besides, IL-10 secreted by B-1 cells participates of the inflammatory response and confirm that B-1 cells play a role in the wound healing process.